P-Solubilizing Streptomyces roseocinereus MS1B15 With Multiple Plant Growth-Promoting Traits Enhance Barley Development and Regulate Rhizosphere Microbial Population - Chouyia, Fatima Ezzahra; Romano, Ida; Fechtali, Taoufiq; Fagnano, Massimo; Fiorentino, Nunzio; Visconti, Donato; Idbella, Mohamed; Ventorino, Valeria; Pepe, Olimpia (Frontiers in Plant Science, 2020)
Phosphate-solubilizing bacteria (PSB) have been reported to increase phosphate (P) content and plant growth. Their application in agricultural systems is an eco-friendly alternative strategy for limiting negative environmental impact of chemical fertilizers and increasing costs. Therefore, the aim of this study was to isolate and characterize new putative PSB to use as inoculum to enhance plant growth and increase P bioavailability in soil. Sixteen bacteria were isolated from Moroccan oat rhizosphere and were screened for their putative P-solubilization by semi-quantitative agar spot method. The two strains MS1B15 and MS1B13, identified as Streptomyces roseocinereus and Streptomyces natalensis, respectively, showed the maximum phosphate solubilization index (PSI = 1.75 and PSI = 1.63). After quantitative assay to determine phosphate solubilization activity, S. roseocinereus MS1B15 was selected for evaluating its putative plant growth promotion activities including production of siderophores, indole-3-acetic acid (IAA) and amino-cyclopropane-1-carboxylate (ACC) deaminase, nitrogen fixation and antimicrobial activity against soil-borne plant pathogens. Under greenhouse condition, barley plants inoculated with S. roseocinereus MS1B15 significantly increased shoot and ear length as well as available phosphorus in ears and leaves and P and N contents in the soil. Overall results showed that the selected strain S. roseocinereus MS1B15 could represent a potential candidate as biofertilizer to increase plant growth as well as P uptake.